2021
DOI: 10.1007/s10854-021-05521-5
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Ni2P@Ni(OH)2 architectures supported on carbon cloth as battery-type electrodes for hybrid supercapacitors with boosting specific capacitance and cycle stability

Abstract: In this work, a novel binder-free electrode, in which three-dimensional porous Ni2P@Ni(OH)2 nanosheet arrays were in-situ grown on carbon cloth (CC), is rationally designed for supercapacitor applications. In comparison with Ni2P@CC, the Ni2P@Ni(OH)2@CC electrode represents superior electrochemical characteristics: the gravimetric capacitance and areal capacitance are boosted to be 632 C g -1 and 0.73 C cm -2 at 1 mA cm -2 , about 2 and 2.7 times larger than those of Ni2P@CC (321 C g -1 and 0.27 C cm -2 ), res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The Ragone plot (Fig. 6e) and Table S4 (ESI†) showed that the CoP@Ni(OH) 2 //AC had a greater energy density than CoP@Ni(OH) 2 ·0.75H 2 O//AC, 34 NiCoP@C@ Ni(OH) 2 //AC, 35 Ni 2 P@Ni(OH) 2 //AC, 36 and Mn 3 O 4 /Ni(OH) 2 //AC. 37 The long charging/discharging curves, over 10 000 GCD cycles at 5 A g −1 , disclosed that the CoP@Ni(OH) 2 //AC demonstrated superior cycling stability, with only a 1.4% decrease in capacitance compared to the initial specific capacitance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Ragone plot (Fig. 6e) and Table S4 (ESI†) showed that the CoP@Ni(OH) 2 //AC had a greater energy density than CoP@Ni(OH) 2 ·0.75H 2 O//AC, 34 NiCoP@C@ Ni(OH) 2 //AC, 35 Ni 2 P@Ni(OH) 2 //AC, 36 and Mn 3 O 4 /Ni(OH) 2 //AC. 37 The long charging/discharging curves, over 10 000 GCD cycles at 5 A g −1 , disclosed that the CoP@Ni(OH) 2 //AC demonstrated superior cycling stability, with only a 1.4% decrease in capacitance compared to the initial specific capacitance (Fig.…”
Section: Resultsmentioning
confidence: 99%